Elevated circulating adenosine deaminase activity in women with preeclampsia: association with pro-inflammatory cytokine production and uric acid levels - Giorgi, Vanessa S. [UNESP]; Witkin, Steven S.; Bannwart-Castro, Camila F. [UNESP]; Sartori, Maria Salete [UNESP]; Romao-Veiga, Mariana [UNESP]; Borges, Vera Therezinha M. [UNESP]; Peracoli, Jose Carlos [UNESP]; Peracoli, Maria Terezinha [UNESP] (Elsevier B.V., 2016)
Objective: Preeclampsia is a specific disorder of human pregnancy that is associated with hyperuricemia and higher levels of pro-inflammatory cytokines. Adenosine deaminase (ADA) is an enzyme present in all human tissues, and is considered an indicator of cellular inflammation. In the present study we assess whether adenosine deaminase (ADA) activity is altered in women with preeclampsia (PE),and contributes to elevated levels of uric acid and pro-inflammatory cytokine production. Study design: The population studied consisted of 60 women with PE, 30 normotensive pregnant women (NT) and 20 non-pregnant women (NP). Uric acid concentration and ADA activity were determined in the serum. Peripheral blood mononuclear cells (PBMCs) were isolated and evaluated for intracellular nuclear transcription factor kappa B (NF-kappa B) levels and for endogenous tumor necrosis factor-alpha (TNF-alpha) and interleukin-10 (IL-1 beta) production. The data were evaluated with parametric or non-parametric tests with significance set at P < 0.05. Results: ADA levels were higher in the PE group compared with the NT and NP groups (P < 0.001). A positive correlation between ADA and uric acid levels was identified in women with PE (P < 0.001). Endogenous production of IL-1 beta and TNF-alpha, as well as intracellular NF-kappa B levels, were higher in PBMCs from the PE group than from NT and NP women (P < 0.01) and correlated with the ADA concentration in preeclamptic women (P < 0.01). Conclusion: An elevation in ADA activity in women with PE may contribute to their increased levels of uric acid and pro-inflammatory immune activity. (C) 2016 International Society for the Study of Hypertension in Pregnancy. Published by Elsevier B.V. All rights reserved.
Keywords: Adenosine deaminase; IL-1 beta; NF-kB; Preeclampsia; TNF-alpha; Uric acid